Bio-efficiency of compost extracts on the wet rot incidence, morphological and physiological growth of okra (Abelmoschus esculentus [(L.) Moench]) - Siddiqui, Yasmeen; Meon, Sariah; Ismail, Razi; Rahmani, Mawardi; Ali, Asgar (Elsevier, 2008)
An experiment was carried out to investigate the efficacy of rice straw and empty fruit bunch (EFB) of oil palm compost extracts either fortified or unfortified with Trichoderma harzianum on morphophysiological growth and occurrence of Choanephora wet rot of okra. Treatments tested were water (control) (T1), rice straw (RST) compost extract (T2), Trichoderma-enriched RST compost extract (T3),empty fruit bunch of oil palm compost extract (T4), Trichoderma-enriched EFB compost extract (T5), aqueous suspension of Trichoderma (T6), and a fungicide Dithane M-451 (2 g l1 of water) (T7). The experimental results revealed significant variations amongst the treatments in respect of morphological characters, e.g. shoot length, tap root length, number of leaves per plant, and leaf area. The shoot and tap root length, number of leaves per plant, leaf area were significantly (P 0.05) higher in Trichodermaenriched RST compost extracts (T3) followed by Dithane M-451 (T7), Trichoderma-enriched EFB extracts (T5), RST (T2), EFB (T4) and aqueous suspension of T. harzianum (T6) in both Choanephora inoculated and uninoculated (control) plots. Similarly, net photosynthetic rate and chlorophyll content were higher in plants receiving Trichoderma-enriched RST compost extracts (T3) with 76.2% reduction in Choanephora wet rot incidence when compared with rest of the treatments. These experimental results revealed that morpho-physiological characters of okra could be modified by the application of Trichoderma-enriched compost extracts. This suggests that use of Trichoderma-enriched compost extracts would be more beneficial in environmentally friendly okra cultivation and may be used as an alternative to inorganic fertilizers/fungicides to enhance plant growth and reduce disease incidence subsequently, resulting in higher yield.